Hierarchical NiCo2@PEDOT/PMo12 core and shell architectures for high-performance supercapacitors. (6th December 2022) - Zhao, Yanan; Song, Yuli; Wang, Bing; Zhang, Yaqian; Zhu, Xiaoyu; Zhang, Yao; Li, Wenze
ABSTRACT: A lot of attention is being paid to developing new electrode materials for energy storage with good stability and excellent specific capacitance. This work involves hydrothermal and oxidation processes to grow NiCo2 @PEDOT/PMo12 materials on carbon cloth. At 20 mA cm −2, the prepared electrodes show an extremely high capacitance of 3476 mF cm −2 . The results prove that NiCo2, PEDOT, and PMo12 ternary components synergized to promote electron transport and electrolyte diffusion. The SC device presents a high energy density of 0.41 mW h cm −3 at a power density of 8.57 mW cm −3, and cycle stability test shows 108.1 % after 600 cycles and 74.5 % after 6000 cycles. In addition, the capacitance of the ASC device is smaller than that of the SC, but the device retains 101.4 % of its initial capacitanc after 10000 cycles at 2 mA cm −2    .